Peculiarities of the inter-municipal cooperation in France - V. A. Tsykalov; K. I. Kuzmenkov (Мир новой экономики, 2018)
The article dwells on the peculiarities of the organization of inter-municipal co-operation in France. This research is subject to analize the structure of interaction of municipal institutions, based on the data about the development of french agglomerations. Objective of the research: to determine possible development directions of inter-municipal cooperation in the Russian Federation by analizing the French regional development policy. Processing of statistical information, which allowed to give qualitative characteristics of the organization of inter-municipal cooperation in France, was carried out in this research; Thus also helped to determine its role in the economic development of France and especially in its metropolitan regions. There were used the methods of analysis, synthesis, comparison, systematic observation and other methods of cognition. It was concluded, that in spite of the constructional complexity of inter- municipal cooperation system in France positive results still has been achieved. The possibility of using foreign experience in Russia was also revealed. Peripheral territories of the largest cities in metropolitan areas exhibit tendency to transform into agglomerations, so, in this terms, organization of low-leveled, decentralized and efficient structure of inter-municipal cooperation was identified as a main goal. Experience of the Big Paris metropolitan area was used and reviewed in the article as the main example of agglomeration development. Keywords: France, Big Paris, agglomeration, regional development.